Leveraging Big Data for Competitive Advantage: A Review in Business Analytics - Baottong, Mozes Haryanto; Baharuddin, Ceskakusumadewi; Sari M, Fitri Indah; Sasmita, Halida; Salam, Karta Negara (Advances in Management & Financial Reporting, 2025)
Purpose: This study examines the strategic integration of big data analytics for achieving competitive advantage in business analytics. Research Method: This study employs a mixed-methods approach, integrating a comprehensive literature review with empirical investigation. Quantitative data was collected via surveys from 200 senior executives, data scientists, and IT managers across various industries. Qualitative data were gathered through semi-structured interviews with 30 participants, providing in-depth insights into the strategic, organizational, and cultural factors influencing the implementation of big data. Results and Discussion: The findings reveal that strategic alignment is crucial for the successful implementation of significant data initiatives—companies with clear strategic alignment report higher returns on investment. Big data significantly enhances customer segmentation, targeting, and personalization in marketing, while also improving supply chain visibility and resilience. However, challenges such as the skills gap, data quality issues, and security concerns impede effective utilization. The study emphasizes the importance of fostering a data-driven culture and implementing robust data governance frameworks. The discussion links these findings with theoretical concepts, supporting hypotheses, and prior research, highlighting the need for integrated frameworks that align significant data initiatives with business strategies. Implications: The study provides practical guidelines for organizations to enhance their competitive advantage by leveraging big data. Recommendations include developing integrated strategies, investing in training programs, promoting data literacy, and ensuring high data quality and security. Addressing these challenges enables organizations to leverage big data analytics for a sustained competitive advantage fully.